The Creation and Application of Disposal Techniques for Handling Scuffles and Embraces Encountered during On-site Law Enforcement - Huang, Ye (Quality in Sport, 2025)
Encountering struggles and hugs from law enforcement targets during the process of law enforcement is one of the most troublesome and thorny issues for police officers. Due to the diversity of law enforcement targets and the uncertainty of their nature, it is difficult for on-site law enforcement police officers to take compulsory measures. Therefore, incidents where Chinese public security police officers often encounter struggles and hugs during on-site law enforcement, fall into a passive situation, and are then surrounded and beaten, resulting in injuries or disabilities, occur from time to time. This is an issue that we must currently face and resolve.